2022
DOI: 10.1007/s12021-022-09572-9
|View full text |Cite
|
Sign up to set email alerts
|

How Machine Learning is Powering Neuroimaging to Improve Brain Health

Abstract: This report presents an overview of how machine learning is rapidly advancing clinical translational imaging in ways that will aid in the early detection, prediction, and treatment of diseases that threaten brain health. Towards this goal, we aresharing the information presented at a symposium, “Neuroimaging Indicators of Brain Structure and Function - Closing the Gap Between Research and Clinical Application”, co-hosted by the McCance Center for Brain Health at Mass General Hospital and the MIT HST Neuroimagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 166 publications
0
10
0
Order By: Relevance
“…Further longitudinal studies with longer follow-ups are needed to evaluate clinical consequences (e.g., initial infection vs. reinfection, prevaccination vs. postvaccination COVID infection) and neuroabnormalities [ 139 , 140 ] as well as other regional implications of neurological relevance (e.g., spinal involvement). Studies have reported the increasing adoption of machine learning techniques in the medical field due to their high accuracy [ 141 , 142 ]. Therefore, future work should include machine learning algorithms to predict the impact of COVID-19 on affected brain and spinal regions [ 143 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further longitudinal studies with longer follow-ups are needed to evaluate clinical consequences (e.g., initial infection vs. reinfection, prevaccination vs. postvaccination COVID infection) and neuroabnormalities [ 139 , 140 ] as well as other regional implications of neurological relevance (e.g., spinal involvement). Studies have reported the increasing adoption of machine learning techniques in the medical field due to their high accuracy [ 141 , 142 ]. Therefore, future work should include machine learning algorithms to predict the impact of COVID-19 on affected brain and spinal regions [ 143 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, machine-learning (ML) approaches as a branch of artificial intelligence have been used in clinical applications to facilitate predictive diagnoses and thereby help treatment plans ( Ahmed et al, 2020 ). In neuroscience, ML algorithms have shown great promise in combining multimodal neuroimaging data and analyzing brain structural and functional alteration at the individual level, suggesting their high translational potential clinically ( Janssen et al, 2018 ; Senders et al, 2018 ; Singh et al, 2022 ). The support vector machine (SVM), one of the popular supervised ML algorithms, recently has been increasingly used in the classification of neurodegenerative diseases applying to a range of MRI modalities and promising superior classification performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the applications for prediction and diagnostics in healthcare 10 14 , ML for brain imaging has application possibilities in the contexts of learning and education 7 , 2 . For decades, scientists have studied the brain processes during cognitive tasks, like mathematics or language.…”
Section: Introductionmentioning
confidence: 99%